Translational medical research and liver transplantation: systematic review - Nacif, Lucas Souto; Kim, Vera; Galvão, Flavio; Ono, Suzane Kioko; Pinheiro, Rafael Soares; Carrilho, Flair José; D’Albuquerque, Luiz Carneiro (Translational Gastroenterology and Hepatology; Vol 3 (November 2018): Translational Gastroenterology and Hepatology, 2018)
Translational medicine has become a priority, but there is still a big difference between the arrival of new treatments and investment. Basic science should not be neglected because the translation from basic research is not sustained in the absence of basic research. The purpose of this literature review was to analyze the translational medicine in the liver transplant field: liver ischemia-reperfusion injury (IRI), immunosuppression, clinical and surgical complications, small-for-size syndrome (SFSS), rejection, and ongoing innovations (liver machine, liver preservation, artificial livers, and regenerative medicine). We performed a systematic literature review that were updated in October 2016. The searches were performed in the Cochrane Central Register of Controlled Trials and Review, PubMed/Medline, Embase, and LILACS databases. All the selected studies on the management of translational medical research in liver transplantation (LT) were analyzed. Initially the search found 773 articles. Methodological viewing and analysis of the articles, followed by the application of scientific models, including translational medicine in the liver transplant field. In conclusions, this review demonstrates the application of scientific research with translation medical benefits regarding the LT. The literature has a great tendency, improvements and investments in the study of translational medicine in LT. Innovative studies and technologies from basic science help to clarify clinical doubts. Moreover, evidence increases the importance of scientific research in quality of clinical practice care.